Around and beyond the square of opposition - Jacquette, Dale; Béziau, Jean-Yves (Studies in Universal Logic, 2012)
The theory of oppositions based on Aristotelian foundations of logic has been pictured in a striking square diagram which can be understood and applied in many different ways having repercussions in various fields: epistemology, linguistics, mathematics, sociology, physics. The square can also be generalized in other two-dimensional or multi-dimensional objects extending in breadth and depth the original Aristotelian theory. The square of opposition is a very attractive theme which has been going through centuries without evaporating. Since 10 years there is a new growing interest for the square due to recent discoveries and challenging interpretations. This book presents a collection of previously unpublished papers by high level specialists of the square from all over the world.